2014
DOI: 10.2522/ptj.20130048
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Respiratory and Limb Muscle Strength and Size in Patients With Sepsis Who Are Mechanically Ventilated

Abstract: When measured at bedside, survivors of sepsis and a period of mechanical ventilation may have respiratory muscle weakness without remarkable diaphragm wasting. Furthermore, deficits in peripheral muscle strength and size may exceed those in the diaphragm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 51 publications
4
93
1
8
Order By: Relevance
“…Ultrasonography is both a feasible and timeefficient tool for use in the clinical setting. At baseline, levels of muscle thickness and CSA were similar to those previously reported in studies examining healthy individuals [12,25,26]. Muscle wasting occurred in this study despite usual care rehabilitation being provided.…”
Section: Discussionsupporting
confidence: 85%
“…Ultrasonography is both a feasible and timeefficient tool for use in the clinical setting. At baseline, levels of muscle thickness and CSA were similar to those previously reported in studies examining healthy individuals [12,25,26]. Muscle wasting occurred in this study despite usual care rehabilitation being provided.…”
Section: Discussionsupporting
confidence: 85%
“…Significantly, the majority of included studies were published between 2012 and 2013 (32,34,35,37), indicating the emerging research interest in ultrasound as a technique for evaluating peripheral skeletal muscle architecture during critical illness. Five studies were European (33,(35)(36)(37)39), with one conducted in Australia (32) and one in North America (34). Patient characteristics of included studies are reported in Table 4.…”
Section: Study Characteristicsmentioning
confidence: 97%
“…None of the seven included studies (32)(33)(34)(35)(36)(37)(38) were RCTs. Six were primarily single group studies, classified as case series (33)(34)(35)(36)(37)(38).…”
Section: Study Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations